Perbedaan Efektivitas Leaflet dan Cakram Gizi terhadap Pengetahuan, Kepatuhan Diet, dan Kadar Glukosa Darah Pasien Diabetes Mellitus Tipe 2 - putri, elvina; Widajati, Endang; Palupi, Fitria Dhenok (NUTRITURE JOURNAL, 2025)
Abstract Background: Diabetes Mellitus (DM) is the seventh leading cause of death globally, with a prevalence of 422 million cases according to the WHO, and ranks as the third leading cause of death in Indonesia due to complications. Poor knowledge about DM accelerates the onset of complications. Educational media serve to facilitate the delivery of health information. Patient knowledge about DM is crucial for long-term disease management. This study aims to compare the effectiveness of leaflet and cakram media in improving knowledge, dietary adherence, and blood glucose levels among patients with type 2 DM at Kedungkandang Health Center. Objective: This study aims to compare the effectiveness of using leaflet and cakram media on knowledge, dietary adherence, and blood glucose levels of outpatients with type 2 Diabetes Mellitus at Kedungkandang Health Center, Malang City. Methods: This research employed a quantitative approach with an experimental design using a two-group pretest-posttest design. The study was conducted in June 2024 at Kedungkandang Health Center, Malang City. The study population consisted of outpatients with type 2 Diabetes Mellitus at the center, with a sample of 12 patients in the control group and 12 patients in the intervention group. Results: The Cakram was found to be more effective than the leaflet in improving knowledge, but it was not yet effective in enhancing dietary adherence, resulting in unstable blood glucose levels. Conclusion: The study concluded that the cakram was more effective than the leaflet in increasing knowledge but was not yet effective in improving dietary adherence, leading to persistently unstable blood glucose levels. Keywords: Cakram, Type 2 DM, Leaflet, Educational media,